Financial Sector Assessment Program : IEG Review of the Joint World Bank and IMF Initiative - Independent Evaluation Group (Washington, DC: World Bank, 2012)
The Financial Sector Assessment Program (FSAP) is a major initiative, undertaken jointly by the World Bank and the IMF, in response to the financial crises of the late 1990s. The ultimate objectives of the program are (i) the identification and resolution of financial sector vulnerabilities and their macroeconomic stability implications; and (ii) fostering financial sector development and its contribution to economic growth. In addition, the FSAP was expected to help the Bank, Fund, and other institutions design appropriate assistance to address issues identified by the FSAP.